5 questions on being a new manager - Ruma, Laurel; Loop, Michael; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2018)
"In this 5 Questions interview, Laurel Ruma talks to Michael Loop about being a new manager."--Resource description page.
Title from resource description page (Safari, viewed March 13, 2018).
Presenter, Laurel Ruma.
Keywords: Management -- Vocational guidance; Electronic books